Comparative study on corneal epithelium healing: effects of crosslinked hyaluronic acid and amniotic membrane extract eye drops in rats - Gonçalves e Souza, Lenara; Vilardo Lóes Moreira, Matheus; Sayuri Saçaki, Claudia; Perlmann, Eduardo; Guimarães Lopes, Thacyana Beatriz; Ferreira, Enio; Moreno, Juan Carlos Duque; Montiani-Ferreira, Fabiano (Frontiers in Veterinary Science, 2024)
Introduction Corneal ulcers are common lesions in both human and veterinary medicine. However, only a few studies have evaluated the efficacy of cross-linked hyaluronic acid (X-HA) eye drops on corneal wound healing. To our knowledge, this is the first study to demonstrate and compare the efficacy of amniotic membrane extract eye drops (AMEED) and X-HA for corneal wound healing in rats. Material and methods A total of 15 male Wistar rats (30 eyes) were used in this study. Then, 10 eyes were treated with X-HA, AMEED, or 0.9% saline. After general and topical anesthesia, a superficial corneal ulcer was created using a corneal trephine. The defect was further polished with a diamond burr. Three groups of 10 eyes each were treated with either one drop of 0.75% X-HA or AMEED or 0.9% saline (control), administered every 12 h for a duration of 72 h. The median epithelial defect area (MEDA), expressed as a percentage of the total corneal surface, was measured at 0, 12, 24, 36, 48, and 72 h. Re-epithelization time scores were also evaluated. The Kruskal–Wallis test was used to compare median times for re-epithelization and histopathologic scores between groups, while the Friedman test (for paired data) was employed to compare results from the serial analysis of MEDA and vascularization scores between groups. Results MEDA was not significantly different between X-HA and AMEED. However, MEDA was significantly smaller in the X-HA group compared to the control group at 36 h (2.73 interquartile range (IQR) 5.52% x 9.95 IQR 9.10%, P=0.024) and 48 h (0.00 IQR 0.26% x 6.30 IQR 8.54%, P=0.030). The overall time for re-epithelization was significantly lower in the X-HA group (3.00 IQR 3.00) compared to the AMEED (6.5 IQR 3.00) and control (7.00 IQR 1.00) groups (P=0.035). Vascularization, hydropic degeneration, and epithelial-stromal separation were significantly less observed in samples in the X-HA-treated compared to samples in the AMEED- and saline-treated groups. Significantly more corneal epithelium cells were labeled for caspase3 in samples from the AMEED- and saline-treated groups compared to those from the X-HA-treated group. Discussion Topical X-HA has been shown to accelerate corneal epithelial healing. AMEED did not decrease corneal re-epithelialization time. X-HA may also potentially be used as an adjunct therapy for treating corneal ulcers in clinical situations.